Effect of intravenous thrombolysis on core growth rate in patients with acute cerebral infarction - Wang, Xueqi; Zhang, Hao; Wang, Qi; Li, Gang; Shen, Hao; Xiao, Yaping; Xu, Luran; Long, Yuming; Chen, Chen; Huang, Zhengyu; Zhang, Yue (Frontiers in Neurology, 2023)
Objective This study aimed to investigate the effects of recombinant tissue plasminogen activator intravenous thrombolysis (IVT) on the core growth rate of acute ischemic stroke. Methods Stroke patients with large vessel occlusion and non-recanalization from IVT treatment were retrospectively included in this study and divided into two groups: IVT and non-IVT. The core growth rate was estimated by the acute core volume on perfusion CT divided by the last known well time from stroke to CT perfusion. The primary endpoint was the core growth rate, the tissue outcome was 24 h-ASPECTS, and the clinical outcome was a 3-month modified Rankin score. Results A total of 94 patients were included with 53 in the IVT group and 41 in the non-IVT group. There was no significant difference in age, gender, hypertension, diabetes, atrial fibrillation, acute NIHSS, and last known well time from stroke to CT perfusion acquisition between the two groups. The core growth rate in the IVT group was lower than that in the non-IVT group, which was statistically significant after multivariate adjustment (coefficient: −5.20, 95% CI= [−9.85, −0.56], p = 0.028). There was a significant interaction between the IVT and the collateral index in predicting the core growth rate. The analysis was then stratified according to the collateral index, and the results suggested that IVT reduced the core growth rate more significantly after the worsening of collateral circulation (coefficient: 15.38, 95% CI= [−26.25, −4.40], p = 0.007). The 3-month modified Rankin score and 24 h-ASPECTS were not statistically significant between the two groups. Conclusion Intravenous thrombolysis reduces the core growth rate in patients with AIS, especially those with poor collateral status.